Tanshinone Inhibits NSCLC by Downregulating AURKA Through Let-7a-5p - Liu, Xiaomin; Zou, Heng; Zhao, Yiqi; Chen, Hang; Liu, Tanglin; Wu, Zong; Yang, Chenghao; Li, Qian; Li, Yanli (Frontiers in Genetics, 2020)
Lung cancer is the most deadly malignancy in the last decade, accounting for about 1.6 million deaths every year globally. Tanshinones is the constituent of salia miltiorrhiza, it has been found that they influence tumorigenesis. However, the role of tanshinones on lung cancer is still not clear. Let-7a-5p, a short noncoding RNA, is regarded as a suppressor gene in tumorigenesis. Herein, we verified that let-7a-5p is significantly downregulated in non-small cell lung cancer (NSCLC) tissues and cell lines. Tanshinone suppressed the expression of aurora kinase A (AURKA), inhibited cell proliferation and arrested cell cycle progression. Our results showed that tanshinones suppressed NSCLC by up-regulating the expressions of let-7a-5p via directly targeting AURKA. Besides, the data reveals that the knockdown of AURKA can also inhibit cell proliferation, arrest cell cycle and promote cell apoptosis. Furthermore, this study demonstrates that AURKA was negatively correlated with let-7a-5p in NSCLC patient tissues. Taken together, our findings suggest that tanshinone inhibits NSCLC by down-regulating AURKA through let-7a-5p. Tanshinones and let-7a-5p have the potential to be candidates for drug development of NSCLC. In conclusion, this study revealed that tanshinones with miRNAs linking leads to partial mechanism in NSCLC.